Possible visualization of a superfluid vortex loop attached to an oscillating Beam - Zemma, E.; Tsubota, M.; Luzuriaga, J. (Springer Nature, 2015)
Fil: Zemma, E. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina